PARANOIA AND PARANOID ANXIETY: : CRITIQUE OF THE NORMAL AND PATHOLOGICAL BASED ON THE WORK OF GEORGES CANGUILHEM (PRÁXIS EM SAÚDE, 2025)
This study investigates paranoia and paranoid anxiety through the dialogue between Freudian psychoanalysis and Canguilhem’s epistemology, analyzing how this articulation can reframe the clinical understanding of the phenomenon. Based on the Freudian conception that understands paranoia as a defense mechanism grounded in the projection of repressed desires, and on Canguilhem’s critique of the rigid dichotomy between normal and pathological (where the pathological emerges as an alternative vital normativity), it is demonstrated that paranoia can be reinterpreted not as a mere disorder, but as a complex strategy of psychic adaptation. The results show that both perspectives, although distinct, converge in emphasizing the contextual and adaptive dimension of the paranoid experience, questioning purely medicalizing approaches. It is concluded that the integration of these approaches provides a more fertile interpretative framework for clinical practice, capable of articulating unconscious determinations (Freud) with singular existential conditions (Canguilhem), thus proposing an evaluation that transcends diagnostic reductionism without denying the specificity of suffering.